Le cinéma, outil d’éducation et d’enseignement de la révolution sous le régime du parti unique en Turquie - Özgür Adadağ (Revue des Mondes Musulmans et de la Méditerranée)
After the republic was founded, the leaders of the « New Turkey » put into place a public education policy that would, among other things, explain and teach the revolution and its achievements. Kemalist executives, aware of the importance of cinema and wishing to make it a tool for social and political education, passed a series of laws in the 1930s and organized free screenings of films in the People's Houses. However, the leaders of the time also reinforced film control mechanisms, particularly at the beginning of the Second World War, in 1939. As a result, the state policy towards cinema, oscillating between a favorable support policy and a firmly restrictive policy led to a limited usage of that art. This study also shows the gap between the ambitions of the founding fathers and the practical implementation of these objectives the period of single-party rule (1923-1946).